A national survey of barriers and facilitators to medications for opioid use disorder among legal-involved veterans in the Veterans Health Administration. Issue 1 (1st December 2022) - Taylor, Emmeline N.; Timko, Christine; Binswanger, Ingrid A.; Harris, Alex H. S.; Stimmel, Matthew; Smelson, David; Finlay, Andrea K.
Abstract: Background: Medications for opioid use disorder (MOUD) are clinically effective at treating OUD among legal-involved populations. However, research shows that legal-involved veterans who receive care through the VHA have lower rates of MOUD use compared to non-legal-involved veterans. Education may be a key factor in intervention strategies to improve MOUD access. This study was a national survey of VHA staff to identify barriers to and facilitators of MOUD, as well as MOUD-related education needs for VHA staff, community partners, criminal justice partners, and legal-involved veterans. Method : A 98-item online survey was conducted to examine VHA staff perspectives ( N  = 218) around needed education, barriers to, and facilitators of MOUD for legal-involved veterans. Descriptive statistics were conducted and linear regression analyses were used to evaluate differences in perceptions by respondents' current position at the VHA and their VHA facility's rate of provision of MOUD among legal-involved veterans. Results : Respondents endorsed a need for education in all areas of MOUD (e.g., existing medications for the treatment of OUD) for VHA staff and providers, community partners, criminal justice partners, and legal-involved veterans. VHA staff perceived barriers to MOUD for legal-involved veterans to include stigma and complicated guidelines around MOUD and OUD treatment. Facilities with low rates of MOUD use highlighted barriers including MOUD conflicting with the philosophy of the local VHA facility and provider stigma toward patients with OUD. Perceptions of efficacy of MOUD differed by respondents' current position at the VHA such that substance use disorder treatment providers perceived buprenorphine and methadone as more effective compared to Veterans Justice Specialists. Conclusion : The results of this study suggest a need for an educational intervention emphasizing the evidence supporting use of MOUD as a lack of knowledge about these medications was considered a barrier to access, whereas gaining education about MOUD was a facilitator to access. Education strategies specifically tailored to address VHA facility-level differences may help address barriers to MOUD experienced by legal-involved veterans.